A comparison of microstructure and mechanical properties of welded thin Ti6Al4V with three different types of laser. (May 2015) - Fan, Y.; Chen, Z.; Zhang, C. H.; Liu, A. M.
Abstract : Many items of medical, aeronautical, electronic and military equipment are exposed to corrosive conditions, and it is a common practice to protect these in laser beam welded titanium-alloy micro-packages, which require very small and precise weld zones. A range of laser types has been applied to this task, including Nd:YAG, diode and (more recently) fibre lasers. Compared with other laser beam welding (LBW) processes, fibre lasers are widely recognised to result in lower overall heat input, a narrower weld zone, less distortion and high process efficiency. This paper contrasts the mechanical and metallurgical properties of laser welded titanium alloy (Ti6Al4V) in the form of thin (0·7 mm) sheet, typical of that used in micro-packages. Welds were produced with three different laser types, namely, Nd:YAG, diode and fibre lasers. Despite the widely accepted advantages of fibre laser processing, weld quality following processing with a Nd:YAG laser was found to be higher than that of welds produced with either the fibre laser or diode laser; welds processed with the fibre laser exhibited serious porosity defects because of excessive laser-workpiece traverse speeds, nor large spot diameter and poor beam quality characteristic of diode lasers.